Affordable housing and urban regeneration in Portugal: a troubled tryst? - Branco, Rosa (2015)
The process of decline in historic city centres has been inseparable from the decline in the resident population, significantly among families with greater purchasing power. Statistical data on population and housing show that the historic centres of Lisbon and Porto have maintained a recessive demographic trajectory over recent decades. Despite some signs of sporadic residential gentrification, the local social fabric continues to be characterized by an ageing population and weak educational and socio-economic capital. In the current phase of economic and social crisis, it is critical to consider whether and how the new agents of urban regeneration, in particular the Urban Rehabilitation Societies, are providing affordable housing in these areas. In this context, it makes sense to discuss the meaning of concepts and models of social and affordable housing in Portugal since they are key elements in the analysis of the sustainability and social relevance of current strategies.